2019
DOI: 10.1101/872150
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Male accessory gland factors increased sex pheromone titres in the glands ofSpodoptera liturafemale moths by inhibiting calling behavior

Abstract: 14Moths are the most widely studied example of pheromones in animals. However, 15 little is known about the mechanism of intrasexual and mating-related intersexual 16 regulation of pheromone production and release in female moths. Our previous 17 studies in Spodoptera litura found that mating induced a higher sex pheromone titre in 18 the pheromone gland (PG) and mating or male accessory gland (MAG) extract 19 suppressed female calling behavior. We therefore hypothesize that the inhibition of 20 female cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Lu et al (2017) showed that mating resulted in a higher sex pheromone titer in the pheromone gland (PG) of S. litura [51]. Later, Xu et al (2019) attributed the suppression of female calling behavior to mating and MAG factors, which resulted in higher sex pheromone titers in mated S. litura females, presumably due to a lower release of pheromones [78]. This implied that irradiation probably influenced MAG factors that might have consequently failed to suppress female calling behavior effectively when mated to F 1 males due to insufficient or less effective ejaculate.…”
Section: Remating Behavior In Response To First Mating With Irradiate...mentioning
confidence: 99%
“…Lu et al (2017) showed that mating resulted in a higher sex pheromone titer in the pheromone gland (PG) of S. litura [51]. Later, Xu et al (2019) attributed the suppression of female calling behavior to mating and MAG factors, which resulted in higher sex pheromone titers in mated S. litura females, presumably due to a lower release of pheromones [78]. This implied that irradiation probably influenced MAG factors that might have consequently failed to suppress female calling behavior effectively when mated to F 1 males due to insufficient or less effective ejaculate.…”
Section: Remating Behavior In Response To First Mating With Irradiate...mentioning
confidence: 99%